Measuring liquidity in agricultural land markets - Marlene Kionka; Martin Odening; Jana Plogmann; Matthias Ritter (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2020)
This paper contributes to the sparse empirical literature on measuring liquidity in agricultural land markets. Using data from Lower Saxony (Germany), we inspect the spatial and temporal variability of various liquidity indicators. We apply a panel vector autoregression (VAR) and Granger causality tests to examine the relationship between liquidity and prices and to identify further determinants of land market liquidity, such as supply shocks and clientele effects. Unlike in housing markets, no positive relationship between prices and market liquidity exists. We conclude that in agricultural land markets, a high demand from expanding farms absorbs supply shocks regardless of prevailing prices.
urn:nbn:de:kobv:11-110-18452/22867-2
Keywords: Q13; Q24; C32; C33; 330; Agricultural land markets; liquidity indicators; panel vector autoregressive model; Granger causality